Fabrication of thin film composite forward osmosis hollow fiber membranes - Fang, Wangxi (2010)
Forward osmosis (FO) has received intensive studies recently for a range of potential applications such as wastewater treatment, water purification and seawater desalination. One of the major challenges to be overcome is the lack of an optimized FO membrane that can produce a high water flux comparable to commercial reverse osmosis (RO) membranes. The objective of the project is to fabricate thin film composite (TFC) hollow fiber membranes which are suitable for FO applications.